Analysis of Employee Communication Ethics on The Performance of The Personnel Bureau of The General Secretary of The Ministry of Defense of The Republic of Indonesia - Siwi Pamungkas, Wilogo; Yulianti, Elis (PT. Multidisciplinary Press Indonesia, 2025)
The purpose of this research is to analyze the communication ethics of employees in the Directorate of Personnel Bureau of the Ministry of Defence of the Republic of Indonesia verbal communication, to analyze the communication ethics of employees in the Directorate of Personnel Bureau of the Ministry of Defence of the Republic of Indonesia in using nonverbal communication, and to analyze the application of communication ethics through the principles of communication ethics of employees in the Directorate of Personnel Bureau of the Ministry of Defence of the Republic of Indonesia. The method used is descriptive qualitative. Data were obtained through interviews and observations with Civil Servants (ASN) and military personnel related to this research in the Directorate of Personnel Bureau of the Ministry of Defence. The results show that (1) Employees' practice of communication ethics in the Directorate of Personnel Bureau of the Ministry of Defence of the Republic of Indonesia positively influences verbal communication, creating a harmonious work environment with polite, clear, and respectful language, and demonstrating integrity. This ethics is also evident through online media practices, strengthening effective communication and shaping a productive and ethical work environment. (2) Nonverbal communication ethics in the Directorate of Personnel Bureau of the Ministry of Defence of the Republic of Indonesia maintain integrity, credibility, and respect for ethical principles through body gestures and attitudes crucial for an efficient, harmonious work environment in line with ethical principles. Training and adaptation to workplace norms support awareness of body language and nonverbal expression, strengthening understanding of communication ethics. (3) The application of communication ethics in the Directorate of Personnel Bureau of the Ministry of Defence of the Republic of Indonesia positively impacts organizational culture, integrity, and public trust. Employees can build an inclusive, transparent, and accountable work culture by adhering to ethical principles in daily interactions, supporting organizational integrity, and positive stakeholder relations. Communication plays a vital role in organizations, especially in the Directorate of Personnel Bureau of the Ministry of Defence of the Republic of Indonesia.